The β-Lactamase Assay: Harnessing a FRET Biosensor to Analyse Viral Fusion Mechanisms - Jones, Daniel M. (Sensors (Basel), 2016)
The β-lactamase (BlaM) assay was first revealed in 1998 and was demonstrated to be a robust Förster resonance energy transfer (FRET)-based reporter system that was compatible with a range of commonly-used cell lines. Today, the BlaM assay is available commercially as a kit and can be utilised readily and inexpensively for an array of experimental procedures that require a fluorescence-based readout. One frequent application of the BlaM assay is the measurement of viral fusion—the moment at which the genetic material harboured within virus particles is released into the cytosol following successful entry. The flexibility of the system permits evaluation of not only total fusion levels, but also the kinetics of fusion. However, significant variation exists in the scientific literature regarding the methodology by which the assay is applied to viral fusion analysis, making comparison between results difficult. In this review we draw attention to the disparity of these methodologies and examine the advantages and disadvantages of each approach. Successful strategies shown to render viruses compatible with BlaM-based analyses are also discussed.